An automatic programming tool for heterogeneous - Tavares, Adriano (1997)
Recent advances in network technology and the higher levels of circuit integration due to VLSI have led to widespread interest in the use of multiprocessor systems in solving many practical problems. As the hardware continues to diminish in size and cost, new possibilities are being created for systems that are heterogeneous by design. Parallel multiprocessor architectures are now feasible and provide a valid solution to the throughput rates demands of the increasing sophistication of control and/or instrumentation systems. Increasing the number of processors and the complexity of the problems to be solved makes programming multiprocessor systems more difficult and error-prone. This paper describes some parts already implemented (mainly the scheduler) of a software development tool for heterogeneous multiprocessor system that will perform automatically: code generation, execution time estimation, scheduling and handles the communication primitive insertion.